30 Years of Flipping the Coin—Heads or Tails? - Svetanoff, Wendy Jo; Dorman, Robert M.; Dekonenko, Charlene; Osuchukwu, Obiyo O.; Hendrickson, Richard J.; Fraser, Jason D.; Oyetunji, Tolulope A.; St Peter, Shawn D. (European Journal of Pediatric Surgery, 2020)
Introduction Swallowed coins are a frequent cause of pediatric emergency department visits. Removal typically involves endoscopic retrieval under anesthesia. We describe our 30-year experience retrieving coins using a Foley catheter under fluoroscopy (“coin flip”).Materials and Methods Patients younger than 18 years who underwent the coin flip procedure from 1988 to 2018 were identified. Failure of fluoroscopic retrieval was followed by rigid endoscopic retrieval in the operating room. Detailed subanalysis of patients between 2011 and 2018 was also performed.Results A total of 809 patients underwent the coin flip procedure between 1988 and 2018. Median age was 3.3 years; 51% were male. The mean duration from ingestion to presentation was 19.8 hours. Overall success of removal from the esophagus was 85.5%, with 76.5% of coins retrieved and 9% pushed into the stomach. All remaining coins were retrieved by endoscopy. Complication rate was 1.2% with nine minor and one major complications, a tracheal tear that required repair. In our recent cohort, successful fluoroscopic removal led to shorter hospital lengths of stay (3.2 vs. 18.1 hours, p < 0.001).Conclusion Patients who present with a coin in the esophagus can be successfully managed with a coin flip, which can be performed without hospital admission, with rare complications.
Keywords: esophageal foreign body; coin ingestion; pediatric; fluoroscopic retrieval